PENERAPAN KONSEP BALANCED SCORECARD DALAM PENGUKURAN KINERJA INSTANSI PEMERINTAH PADA INSTITUT PEMERINTAHAN DALAM NEGERI - rasidi rasidi; Rudi Sadmoko (Jurnal Ilmu Pemerintahan Widya Praja, 2019)
Performance in the public sector is multidimensional and comprehensive, so that the nature of output produced by the public sector is more intangible output, so to measure the performance of the public sector it is necessary to choose a comprehensive performance measurement technique that is the Balanced Scorecard. Research Objectives to describe the application of each Balanced Scorecard perspective in measuring agency performance. The research method used is descriptive qualitative method. IPDN is a public sector organization with a main focus on output that is "producing competent, character and personality cadres of government" which ultimately to serve and improve the welfare of the community. Thus the need for innovative development in implementing a comprehensive organizational performance measurement system that can be implemented by the work unit in measuring the performance of agencies as outlined in the Government Agency Performance Report. The concept of the Balanced Scorecard is integrated into the IPDN Strategic map and then mapped in the perspective mapping matrix, indicators, weights, and sources of measurement data, so that formulations for Organizational Performance Values ​​can be identified. The modification of the Balanced Scorecard method applied by IPDN agencies includes 4 (four) perspectives namely Customer & stakeholders perspective, Financial perspective, Internal business process perspective, and Learning and Growth perspective. Keywords: Balanced Scorecard, Strategic map, performance